Ответы и объяснения

2013-05-01T18:16:07+04:00

\left \{ {{\frac{x}{2}} - \frac{y}{3} =1\ |*6 \atop {\frac{x}{5} - \frac{y}{4} = -1\ |*20}} \right.\\ \\ \left \{ {{3x - 2y =6 \ |*4 \atop {4x-5y=-20 \ |*(-3)}} \right.\\ \\ \left \{ {{12x - 8y =24 \atop {-12x+15y=60}} \right. \ +\\ \\ 12x-12x-8y+15y=24+60\\ 7y=84\\ y=12\\ 3x-2*12=6\\ 3x-24=6\\ 3x=6+24\\ 3x=30\\ x=30:3\\ x=10

Ответ: (10; 12)

 

Второй аналогично все делается.

Лучший Ответ!
2013-05-01T18:38:28+04:00

x/2-y/3=1 умножим на 6

x/5-y/4=1 умножим на 20

3х-2у=6

4х-5у=-20

12х-8у=24

-12х+15у=60

12х-12х-8у+15у=24+60

7у=84

у=12

3х-2*12=6

3х=6+24

х=10

ответ:(10;12)

2)

х/3-у/2=-3

х/2+у/5=5

2х-3у=-90

5х+2у=50

10х-15у=-90

-10х-4у=-100

10х-10х-15у-4у=-90+(-100)

-19у=-190

у=10

5х=2*10=50

5х=30

х=6

ответ:(6;10)